Evaluation of glycogen storage disease as a cause of ketotic hypoglycemia in children. Issue 3 (29th July 2014) - Brown, Laurie M.; Corrado, Michelle M.; van der Ende, Rixt M.; Derks, Terry G. J.; Chen, Margaret A.; Siegel, Sara; Hoyt, Kate; Correia, Catherine E.; Lumpkin, Christopher; Flanagan, Theresa B.; Carreras, Caroline T.; Weinstein, David A.
Abstract: Introduction: Ketone formation is a normal response when hypoglycemia occurs. Since the majority of children with recurrent hypoglycemia cannot be diagnosed with a known endocrine or metabolic disorder on a critical sample, ketotic hypoglycemia has been described as the most common cause of low blood glucose concentrations in children. Critical samples, however, will miss the ketotic forms of glycogen storage disease (GSD), which present with elevated ketones, hypoglycemia, and normal hormonal concentrations. Results: A total of 164 children (96 boys, 68 girls) were enrolled in the study. Prediction of pathogenicity of DNA changes using computer modeling confirmed pathology in 20 individuals [four GSD 0, two GSD VI, 12 GSD IX alpha, one GSD IX beta, one GSD IX gamma] (12 %). Boys were most likely to have changes in the PHKA2 gene, consistent with GSD IX alpha, an X‐linked disorder. Conclusions: Mutations in genes involved in glycogen synthesis and degradation were commonly found in children with idiopathic ketotic hypoglycemia. GSD IX is likely an unappreciated cause of ketotic hypoglycemia in children, while GSD 0 and VI are relatively uncommon. GSD IX alpha should particularly be considered in boys with unexplained hypoglycemia.